Hubungan Pola Asuh dengan Masalah Emosi dan Perilaku pada Anak Kelas 4, 5, dan 6 di SD Negeri 2 Semarapura Tengah Kabupaten Klungkung Bali - I Wayan Eka Arsana; Gede Giofany Achaldy Indra Pradnya Rudi Suryantara; Komang Trisna Sumadewi (Aesculapius Medical Journal, 2023)
In society there are norms that regulate the way children behave according to the stage of growth and development. However, if the child engages in behavior that is not in accordance with the expectations of the community, then the child is considered to have emotional and behavioral problems. Emotional and behavioral problems that occur have an impact on the increase in cases of delinquency and criminality of children. This is inseparable from the parenting pattern given by the parents to their children. This study aims to find out the relationship between parenting patterns and emotional and behavioral problems in grade 4, 5, and 6 children at SD Negeri 2 Semarapura Tengah Klungkung Regency, Bali. The research design used in this study is an analytical method with a cross sectional approach, as well as analyzed using the Contingency Coefficient. Simple random sampling with a sample count of 47 people. The results of the study obtained a p value is < 0,01 in parenting patterns with emotional and behavioral problems, thus having a significant relationship. In conclusion, there is a relationship between parenting patterns and emotional and behavioral problems in 4th, 5th, and 6th graders.